Diagnostic Accuracy of Anthropometric Markers of Obesity for Prediabetes: A Systematic Review and Meta-Analysis - Vera-Ponce, Víctor Juan; Zuzunaga-Montoya, Fiorella E.; Loayza-Castro, Joan A.; Ramirez-Ortega, Andrea P.; Torres-Malca, Jenny Raquel; García-Lara, Rosa A.; Iturregui Paucar, Cori Raquel; Valladares-Garrido, Mario J.; Cruz-Vargas, Jhony A. De La (International Journal of Statistics in Medical Research, 2023)
Introduction: Prediabetes is a significant public health concern due to its high risk of progressing to diabetes. Anthropometric measures of obesity, including body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR) have been demonstrated as key risk factors in the development of prediabetes. However, there is a lack of clarity on the diagnostic accuracy and cut-off points of these measures. Objective: To determine the diagnostic accuracy of these anthropometric measures for their most effective use in identifying prediabetes. Methodology: A systematic review (SR) with metanalysis of observational studies was carried out. The search was conducted in four databases: Pubmed/Medline, SCOPUS, Web of Science, and EMBASE. For the meta-analysis, sensitivity and specificity, together with their 95% confidence intervals (CI 95%) were calculated. Results: Among all the manuscripts chosen for review, we had four cross-sectional studies, and three were classified as cohort studies. The forest plots showed the combined sensitivity and specificity for both cross-sectional and cohort studies. For cross-sectional studies, the values were as follows: BMI had a sensitivity of 0.63 and specificity of 0.56, WC had a sensitivity of 0.59 and specificity of 0.58, and WHtR had a sensitivity of 0.63 and specificity of 0.73. In the cohort studies, the combined sensitivity and specificity were: BMI at 0.70 and 0.45, WC at 0.68 and 0.56, and WHtR at 0.68 and 0.56, respectively. All values are provided with 95% confidence intervals. Conclusions: This systematic review and meta-analysis evaluated the diagnostic accuracy of BMI, WC, and WHtR in identifying prediabetes. The results showed variations in sensitivity and specificity, with WHtR having the highest specificity in cross-sectional studies and BMI having improved sensitivity in cohort studies.